Estudo e descrição de uma nova icnoespécie de artrópode da formação Botucatu (jurássico superior — cretáceo inferior) da bacia do Paraná, Estado de São Paulo, Brasil - Peixoto, Bernardo de Campos Pimenta e Marques (Universidade Federal de São Carlos, 2017)
Here we describe the new ichnospecies Lithographus araraquarensis isp. nov.. A trackway composed by two rows, whose internal width between the rows is less than 1/3 of the external width; with alternating to staggered series, composed of three elliptical tracks that can vary from slightly elongated, tapered or circular. The slabs were found in the Araraquara region, São Paulo State, in the yellowish/reddish sandstones of the Botucatu Formation, interpreted as a testimony of a gigantic aeolian depositional system, a sandsea (erg), with an arid climate that developed during the Late Jurassic to Early Cretaceous in the Center-South part of Gondwana. Through comparisons with neoichnological studies and morphological deduction, the production of these trackways is assigned to the pterygote insects, which have walked over the unconsolidated sandy substrate. Lithographus araraquarensis isp. nov. was probably produced by beetles that had a flexible diet and were part of the fauna of detritivores omnivores that fed on biomass particles that accumulated in the slipface of the dunes of the Botucatu paleodesert, being able to adopt herbivorous and saprophagous diet when opportune. The description of this new trackway amplifies the knowledge about the faunistic composition of the Botucatu paleodesert and provides subsidies to better understand its paleoenvironment and the ecological relations prevailing at the time. Probably, the producer of Lithographus araraquarensis isp. nov., together with the producers of Taenidium isp. and Skolithos linearis, ware a source of food for primary consumers, represented by arachnids, such as scorpions and spiders, and small mammaliforms. The above trophic level was constituted by theropod dinosaurs of the group Coelurosauria and Carnosauria, and large mammaliforms, which predated smaller theropods and dinosaurs of the Ornithopoda group. Any new occurrences of Lithographus araraquarensis isp. nov. in stratigraphic units of other localities, representing other times, should be analyzed in the light of the ichnofacies model. The recurrence of Lithographus araraquaraensis isp. nov. in aeolian units, and with differentiated abundance in relation to non-aeolian units, could indicate an analogous paleoenvironment to the Botucatu Formation, that is, an arid desert. Both the confirmation and the refutation of recurrence would enrich the theoretical framework of the invertebrate ichnofacies Octopodichnus-Entradichnus for eolian environment.
Study and description of a new ichnospecies of arthropod of the Botucatu Formation (late jurassic – early cretaceous) of Paraná basin, São Paulo State, Brazil
Keywords: Mesozoico; Insetos; Eólico; América do Sul; Continental; Deserto; Paleoerg; Gondwana; Mesozoic; Insects; Aeolian; South America; Trackway; Desert; CIENCIAS BIOLOGICAS::ECOLOGIA